Chemical modification of cellulose nanofibers with phthalimide air filter to adsorb carbon dioxide - Sima Sepahvand (Regional Information Center for Science and Technology (RICeST), 2019)
The applications of renewable nanomaterial’s, such as cellulose nanofibers (CNFs), have recently been of great interest due to their unique properties, including high surface area, high aspect ratio, biodegradable, easy access and reactive hydroxyl groups on the surface. The purpose of this study was to fabricate refined air nano filters using phthalimide- modified CNFs. Because phthalimide contains amine groups that are needed to adsorb carbon dioxide. In this study, a freeze drying method was used for direct removal of water from pure CNFs gel and phthalimide -modified. Also, the properties of pure CNFs aerogels and phthalimide-modified (containing amine groups) were investigated to adsorption carbon dioxide. Modification of CNFs with phthalimide in 4% (v/v) acetic acid, with ratios of CNFs to phthalimide 1: 0, 1: 0.5, 1: 1 and 1: 1.5 wt %. Chemical properties and morphology of modified CNFs were investigated using various techniques including SEM, FTIR-ATR, XRD and TGA. Based on the results, the SEM test did not show any change in the size and structure of the modified CNFs. The presence of phthalimide was confirmed by the creation of new pitches NH2, C-N and ester 〖COO〗^- on modified CNFs using the ATR-FTIR spectroscopy test. Also, the results of TGA indicated that increasing the amount of phthalimide reduces the thermal stability, indicating the reactivity of the functional groups of phthalimide with CNFs. In addition, the highest carbon dioxide adsorption of 1.5% phthalimide was about 50%.